PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA DENGAN MENGGUNAKAN MEDIA VIDEO ANIMASI UNTUK SISWA KELAS V SDN 110 PEKANBARU - Aisyah Habibah; Munjiatun; Guslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improving Pancasila Education learning outcomes by using animated video media for Grade V students of SDN 110 Pekanbaru. This type of study is an experimental study with a pre-experimental type with a One Group Pretest-Posttest Design. The sample of this study was 22 students of Class VC. The results of this study are seen from the pretest and posttest scores of the research sample. There is an improving Pancasila Education learning outcomes by using animated video media, based on the results of the study showing the criteria for improving Pancasila Education learning on the indicators of Pancasila values from the average value of N-Gain Score and N-Gain Percent on the value of divinity of 0.6 and 60% which are moderate and quite effective criteria. Humanity values of 1 and 100% which are high and effective criteria. Unity values of 1 and 100% which are high and effective criteria. Democracy values of 0.7 and 70% which are moderate and quite effective criteria. The fairness values of 1 and 100% which are high and effective criteria. Thus, the final results of improving Pancasila Education learning outcomes by using animated video media for Grade V students of SDN 110 Pekanbaru show the criteria for an improving in the average value of N-Gain Score and N-Gain Percent of 0.8 and 80% which are high and effective criteria, it was found that 22 students experienced an improving in the criteria for improving N-Gain Score there are 12 people (55%) with high criteria and 10 people (45%) with medium criteria, as well as from N-Gain Percent there are 12 people (55%) with effective criteria, 8 people (36%) with moderately effective criteria, 1 person (5%) with less effective criteria, and 1 person (5%) with ineffective criteria.